Perbandingan Kadar Haemoglobin pada Ibu Hamil Trimester I, II, III dalam Rangka Mengidentifikasi Kejadian Anemia Puskesmas Gebang Kabupaten Langkat Provinsi Sumatera Utara Tahun 2024 - Nurhajimah Nurhajimah; Erin Padilla Siregar; Sri Rezeki; Amelia Erawaty Siregar (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Around 41.8% of pregnant women around the world experience anemia. The prevalence of anemia in pregnant women in the world is estimated at around 57.1% in Africa, 48.2% in Asia, 25.1% in Europe and 24.1% in America. The results of Basic Health Research (Riskesdas) in 2013, the prevalence of anemia in pregnant women in Indonesia was around 37.1%, with hemoglobin levels < 11.0 g/dL approaching the proportion between urban areas 36.4% and rural areas 37.8%. Based on the 2001 Household Health Survey (SKRT), the prevalence of anemia in pregnant women was 40.1%. Meanwhile, the 2004 DKI Jakarta survey showed that the prevalence rate of anemia in pregnant women was 43.5%. The general aim of this research was to determine differences in hemoglobin levels in pregnant women in the first, second and third trimesters at the Gebang Health Center, Langkat Regency in 2024. Hemoglobin examination in pregnant women aims to To find out whether the mother is experiencing blood deficiency or not, namely by checking hemoglobin levels during pregnancy. The method is quantitative research with an analytical survey method using a cross sectional design, namely, a study that concerns risk factors using a retrospective approach. Analysis shows that there are differences in hemoglobin levels in the first, second and third trimesters. The average hemoglobin levels in the first trimester (11.7 g/dL) and II (11.0 g/dL) were still within normal limits, while the hemoglobin in the third trimester (10.2 g/dL) was abnormal. Hemoglobin levels < 11.0 g/dL in pregnant women can be said to be anemia, whereas if hemoglobin levels in pregnant women are > 11.0 g/dL it is not said to be anemia. So it can be seen that hemoglobin levels in the third trimester are lower than hemoglobin levels in the first and second trimesters. Pregnant women are expected to be able to check their pregnancy by carrying out an HB examination.